Genome wide identification and expression profiling of Bcl2 associated anthanogene family cochaperones reveals abiotic stress response in Ricinus communis L. - Muhammad Arif; Shuzhen Men; Ayesha Fazal Nawaz; Hina Abbas; Wenqi Shi; Mohamed A. El-Sheikh; Parvaiz Ahmad; Ruhong Xu; Luhua Li (Scientific Reports)
Abstract Castor (Ricinus communis L.), a member of the Euphorbiaceae family, is a non-edible oilseed crop extensively cultivated in arid and semi-arid regions worldwide for its diverse industrial uses. The B-cell lymphoma 2 (Bcl-2)-associated athanogene (BAG) family is a diverse and well-conserved co-chaperone family present in both plants and mammals. BAG proteins interact with a wide range of proteins, regulating various functions, including stress response, growth, and development. However, the function of BAGs in oilseed crops like castor remains largely unknown. In this study, we discovered 9 BAG protein family members (RcBAGs) in castor through genome-wide scanning. We investigated chromosomal localization, performed in silico promoter analysis, conducted phylogenetic and synteny analyses, and examined gene architecture. Additionally, we predicted protein–protein interactions and assessed the responses of these genes to various abiotic stresses and hormones. Based on their cellular localization, the RcBAG family was categorized into nuclear, chloroplastic, and cytoplasmic groups. Syntenic gene pairs across different crops also validated the importance and functional conservation of these BAG genes during evolution. Furthermore, in Ricinus communis, the RcBAG genes were scattered unevenly throughout seven of the 10 chromosomes. The study reveals that RcBAG genes are crucial for stress management and castor growth, responding to abiotic stimuli through distinct regulatory pathways. Quantitative real-time polymerase chain reaction (qRT-PCR) investigation revealed that 9 distinct RcBAG genes were strongly induced after cold and heat treatments. Functional analysis and protein–protein interactions were used to predict the potential regulatory network of RcBAGs, revealing tight networking and signaling with HSP proteins. This study provides a foundation for future research into the molecular mechanisms and regulatory processes during R. communis growth, development, response to various stressors, and protein interactions.